Relationship between calcium in atherosclerotic plaques and bone mineral density : a clinical and histological perspective - Cruz, Rafael António Moiteiro da, 1992- (2017)
Trabalho Final do Curso de Mestrado Integrado em Medicina, Faculdade de Medicina, Universidade de Lisboa, 2016